Efeitos da administração de diferentes protocolos anestésicos na eletroejaculação de cutias (dasyprocta leporina linneaus, 1753) - Lima, Amara Gyane Alves de (Universidade Federal Rural do Semi-Árido, 2018)
The objective of this study was to evaluate different anesthetic protocols for the electroejaculation of cutias (Dasyprocta leporina), in order to indicate which is better suited for obtaining spermatozoa and capable of conferring analgesic conditions to the animals. Ten sexually mature males were used and each individual randomly passed through four anesthetic protocols: xylazine / ketamine (G1); xylazine / ketamine / epidural (G2); meperidine / azaperone / xylazine / ketamine / epidural (G3) and dexmedetomidine / ketamine (G4). Heart rate, respiratory rate, systolic, diastolic and mean arterial pressure, temperature, induction latency period and anesthetic recovery were evaluated. Regarding the reproductive parameters, we evaluated the erection, the cycle of stimulation that occurred ejaculation and the seminal variables. The data of physiological parameters were analyzed by ANOVA (Two Way ANOVA RM) for repeated measurements, followed by the Tukey test. Already the semen profile was analyzed, when parametric, by ANOVA (One Way ANOVA RM) for repeated measures followed by Tukey. P <0.05 were considered significant. The G4 group had a lower mean for induction latency, taking (3.16 ± 2.04 minutes) to be placed in the lateral decubitus position and to allow manipulation. Presence of spermatozoa was observed in 30% of ejaculates of G1 animals, 20% of G4, 10% of G2. The G3 group did not provide ejaculate with spermatozoa. G1 provided semen with sperm concentration (270.0 ± 200 x 106) and motility (95.0 ± 0.0) significantly higher than G4. All animals recovered on average 2 hours after anesthetic induction satisfactorily. Anesthesia protocols allowed the electroejaculation procedure to be performed, however, the G2 and G4 groups maintained better vital functions, indicating better analgesia
Keywords: Analgesia; alfa-2 agonistas; sêmen; eletroestimulação; roedores; Analgesia; alpha-2 agonists; semen; electrostimulation; rodents; CIENCIAS AGRARIAS::MEDICINA VETERINARIA